2020
DOI: 10.1186/s12935-020-01697-8
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between ATF2 and NEAT1 contributes to lung adenocarcinoma progression

Abstract: Background Activating transcription factor 2 (ATF2), a member of the activator protein 1 (AP-1) transcription factor family, has been shown to be involved in the pathobiology of numerous cancers. However, the biological role and mechanism of ATF2 in lung adenocarcinoma (LUAD) remains to be elucidated. Methods The expression of ATF2, NEAT1 and miR-26a-5p in LUAD tissues and cell lines was detected by qRT-PCR and western blotting. The interaction bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Four of the top ten loci in lncRNA according to maxHeight are Neat1, and we further confirmed through the RIP experiment that RBM10 can recruit Neat1. One study showed that Neat1 expression increased in LA tissues, and that ATF2 and Neat1 form a positive feedback loop mediated by miR-26a-5p, coordinately contributing to LA progression [ 38 ]. Zhao et al concluded that downregulation of Neat1 in NSCLC inhibits its growth, migration, and invasion through the miR-204/NUAK1 axis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four of the top ten loci in lncRNA according to maxHeight are Neat1, and we further confirmed through the RIP experiment that RBM10 can recruit Neat1. One study showed that Neat1 expression increased in LA tissues, and that ATF2 and Neat1 form a positive feedback loop mediated by miR-26a-5p, coordinately contributing to LA progression [ 38 ]. Zhao et al concluded that downregulation of Neat1 in NSCLC inhibits its growth, migration, and invasion through the miR-204/NUAK1 axis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Realtime PCR was performed using 2 × RealStar Green Fast Mixture (Genstar, Beijing, China) on a CFX96 RealTime PCR system (Bio-Rad, Hercules, CA, USA) according to the manufacturer's instructions. The relative expression levels were calculated using the 2 −ΔΔCt method as previously described [23]. The primer sequences are listed in Additional file 1: Table S1.…”
Section: Quantitative Realtime Pcr (Qrt-pcr)mentioning
confidence: 99%
“…LncRNA NEAT1 plays a carcinogenic role in various tumors, including gastric cancer, lung cancer, colorectal cancer and liver cancer [ 123 ]. Recent studies have shown that NEAT1, as a ceRNA, can be a new target for HCC therapy.…”
Section: The Potential Of Lncrna Related Cernet As Therapy Target In Hccmentioning
confidence: 99%